O ensino de estrutura da matéria na disciplina de física: uma análise de estruturas conceituais para a modelagem do currículo - Prado, Gustavo Ferreira [UNESP] (2015)
From the studies developed in the research group Ensino de Química, Investigação Orientada, Linguagens e Formação Docente, ou Universidade Estadual Paulista Julio de Mesquita Filho - Unesp - campus of Bauru-SP, this work and theoretical frameworks used, it was noticed that most of the high school teachers who teach physics dis not point structure of matter, in their classes, either within the direct approach of the State of São Paulo Curriculum for Natural Sciences. Although, a direct approach to the content (Structure of Matter: models of atoms and molecules, energy quantization, radioactivity and elementary particles), much of the construction of these concepts, which make up part of modern and contemporary physics, begins in philosophy or in the effort to overcome the limitations that the classical approach of science imposes. We believe that the education Structure of Matter depends directly on the joint carried out by Professor between classic and contemporary knowledge of science. This articulation, in turn, depend entirely on the concepts formed by teachers about the treated concepts, ie its ontological vision, epistemological and conceptual theme. Therefore, we invite teachers who taught the discipline of physics in high shool of Bauru-SP region, to build and discuss these concepts in a continuing education course conducted with the research group. Thus, we sought to initially build on the History, Philosophy and Philosophy of Science the concepts underlying the Structure of Matter, to then perform a critical discussion of its relationship with the curriculum of the State of São Paulo and the factors that limited classes that addressed the issue. Later the discussion we conducted a conceptual study directed and teachers built ta lesson plan that would address the issue. Under the survey, this way inserted at specific times of the training course, enabling the holding of discussion concerning the knowledge of teachers...